Glutamatergic neurometabolite levels in the caudate are associated with the ability of rhythm production - Shiori Honda; Yoshihiro Noda; Karin Matsushita; Ryosuke Tarumi; Ryosuke Tarumi; Natsumi Nomiyama; Sakiko Tsugawa; Yui Tobari; Nobuaki Hondo; Keisuke Saito; Masaru Mimura; Shinya Fujii; et al. (Frontiers in Neuroscience, 2023)
IntroductionGlutamatergic neurometabolites play important roles in the basal ganglia, a hub of the brain networks involved in musical rhythm processing. We aimed to investigate the relationship between rhythm processing abilities and glutamatergic neurometabolites in the caudate.MethodsWe aquired Glutamatergic function in healthy individuals employing proton magnetic resonance spectroscopy. We targeted the right caudate and the dorsal anterior cingulate cortex (dACC) as a control region. Rhythm processing ability was assessed by the Harvard Beat Assessment Test (H-BAT).ResultsWe found negative correlations between the production part of the Beat Saliency Test in the H-BAT and glutamate and glutamine levels in the caudate (r = −0.693, p = 0.002) whereas there was no such association in the dACC.ConclusionThese results suggest that higher glutamatergic neurometabolite levels in the caudate may contribute to rhythm processing, especially the ability to produce meter in music precisely.